Isu Proses Bisnis Berbasis Artificial Intelligence untuk Menyosong Era Industri 4.0 - Siregar, Herbert; Setiawan, Wawan; Dirgantari, Puspo Dewi (JURNAL BISNIS STRATEGI, 2020)
Changes in business processes that are running very fast in the industrial era 4.0 have positive and negative impacts on the business world. For those who want to continue to progress and develop, then these changes become a necessity. This study aims to uncover various types of business process models that are currently developing. We conduct investigations from various international journal articles and classify articles according to the field of study. The results of the investigation can provide an overview of the issues that are currently developing in the international world and become one of the references for those engaged in the business world and academia.